2010
DOI: 10.3109/03639040903092335
|View full text |Cite
|
Sign up to set email alerts
|

Development of pH- and enzyme-controlled, colon-targeted, pulsed delivery system of a poorly water-soluble drug: preparation and in vitro evaluation

Abstract: The above results indicated this system could be served as a potential carrier to deliver poorly water-soluble drug specifically to the colon.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…The effect of PPIs was examined by using CT26 mouse colon cancer cells treated with pantoprazole and/or alkaline media[14] (Figure 1). PPI treatment did not affect cell proliferation of CT26 cells regardless of glucose concentration (Figure 1A).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The effect of PPIs was examined by using CT26 mouse colon cancer cells treated with pantoprazole and/or alkaline media[14] (Figure 1). PPI treatment did not affect cell proliferation of CT26 cells regardless of glucose concentration (Figure 1A).…”
Section: Resultsmentioning
confidence: 99%
“…Expression of transforming growth factor (TGF) β and fibroblast growth factor (FGF) 2 was increased by treatment with PPI or alkaline media. TGF-β and FGF2 are known to stimulate collagen-producing fibroblasts[14]. In contrast, expression of replication factor C1 ( RFC1 orAlp145 ), a negative regulator of collagen expression[15], was downregulated by treatment with PPI or alkaline media.…”
Section: Resultsmentioning
confidence: 99%
“…The enzyme degradation kinetics of pectin has been enhanced by blending it with other polymers such as ethylcellulose, hydroxypropylmethylcellulose, chitosan, poly(lysine), and polyacrylate derivatives containing quaternary ammonium groups to take advantage of the enzymatic repertoire of the bacterial flora in the presence of co-encapsulated enzyme co-factors to potentiate their action [183]. Lai and colleagues exposed guar gum to a simulated colonic fluid containing β-mannanase and demonstrated in situ pore generation by ionic interactions and the subsequent cargo release [184]. Other materials used for colon targeting include amylose combined with ethylcellulose, galactomannan, inulin, and dextran [185].…”
Section: Enzyme-responsive Matricesmentioning
confidence: 99%
“…Ionic strength has proven to have a marked effect on charged poly(N-isopropyl acrylamide) (PolyNIPAM) hydrogels, altering their swelling/shrinking behavior [37,184]. In this regard, it has been observed that a strongly charged hydrogel is likely to swell at low ionic strengths due to the strong interchain electrostatic repulsion but shrinks at high ionic strengths due to electrostatic screening effects [187].…”
Section: Ionic Strength and Redox-responsive Matricesmentioning
confidence: 99%
“…Dissolution testing of polysaccharide-based oral colon-targeted delivery systems is a consistent challenge due to the varying pH, viscosity, presence of diverse microbiota, and motility conditions in the upper GI segments that the system needs to traverse before reaching the colon. [ 1 ] This challenge is further intensified by the diverse strategies used in the formulation of colon-targeted delivery systems, their release being designed to be facilitated by stimuli such as pH,[ 2 3 ] pH and time,[ 2 ] presence of enzymes,[ 4 ] time,[ 6 7 8 9 ] using prodrug based,[ 7 ] pressure controlled,[ 10 ] and microbially triggered delivery systems. [ 11 12 13 14 15 16 17 18 ] The most commonly reported medium to evaluate all these types of delivery systems is the one that utilizes colon contents of rodents.…”
Section: Introductionmentioning
confidence: 99%